The Turkish version of the Rome III criteria for IBS is valid and reliable - Özgürsoy Uran, Berna Nilgun; Vardar, Rukiye; Karadakovan, Ayfer; Bor, Serhat (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: In this study, we aimed to provide the usage of the Rome III criteria for irritable bowel syndrome (IBS) in the healthcare field by conducting validity and reliability studies in Turkey and to facilitate diagnosis of these patients. Materials and Methods: Item analysis of the Rome III criteria was performed, and the test was applied to 79 patients after their consistency had been validated with expert opinion. After the first application, the retest was applied to 77 cases, and the consistency between the two applications was examined by kappa analysis. IBS was diagnosed by expert opinion, which was accepted as ’the gold standard’. Results: Cronbach’s alpha of the Rome III criteria was calculated as 0.90. When the compliance between expert assessment and IBS Rome III diagnostic criteria was compared, the diagnostic criteria’s sensitivity was determined as 78.6%, and their specificity was 82.9%. When the Rome III criteria test-retest agreement was analysed, the sensitivity, specificity and negative and positive predictive values of the Rome III diagnostic criteria were determined as 97.4%. Conclusion: In this study, the internal consistency of the Rome III criteria for diagnosis of patients with IBS in our country was found to be an important criterion because of the fact that the Rome III criteria have high internal consistency and validation, they are a reliable measurement tool, they are able to distinguish IBS-positive and -negative cases with the same rate as a specialist and their application is very easy.